Engraftment and proliferation potential of embryonic lung tissue cells in irradiated mice with emphysema - Shiraishi, Kazushige; Shichino, Shigeyuki; Tsukui, Tatsuya; Hashimoto, Shinichi; Ueha, Satoshi; Matsushima, Kouji (Scientific reports, 2019)
Recently, there has been increasing interest in stem cell transplantation therapy, to treat chronic respiratory diseases, using lung epithelial cells or alveolospheres derived from endogenous lung progenitor cells. However, optimal transplantation strategy of these cells has not been addressed. To gain insight into the optimization of stem cell transplantation therapy, we investigated whether lung cell engraftment potential differ among different developmental stages. After preconditioning with irradiation and elastase to induce lung damage, we infused embryonic day 15.5 (E15.5) CAG-EGFP whole lung cells, and confirmed the engraftment of epithelial cells, endothelial cells, and mesenchymal cells. The number of EGFP-positive epithelial cells increased from day 7 to 28 after infusion. Among epithelial cells derived from E13.5, E15.5, E18.5, P7, P14, and P56 mice, E15.5 cells demonstrated the most efficient engraftment. In vitro , E15.5 epithelial cells showed high proliferation potential. Transcriptome analyses of sorted epithelial cells from E13.5, E15.5, E18.5, P14, and P56 mice revealed that cell cycle and cell-cell adhesion genes were highly enriched in E15.5 epithelial cells. Our findings suggest that cell therapy for lung diseases might be most effective when epithelial cells with transcriptional traits similar to those of E15.5 epithelial cells are used.